Recurrent homozygous damaging mutation in , encoding a protein disulfide isomerase, in four families with microlissencephaly. - Ghosh, Shereen Georges; Wang, Lu; Breuss, Martin W; Green, Joshua D; Stanley, Valentina; Yang, Xiaoxu; Ross, Danica; Traynor, Bryan J; Alhashem, Amal M; Azam, Matloob; Selim, Laila; Bastaki, Laila; et al. (J Med Genet, 2020)
BACKGROUND: Protein disulfide isomerase (PDI) proteins are part of the thioredoxin protein superfamily. PDIs are involved in the formation and rearrangement of disulfide bonds between cysteine residues during protein folding in the endoplasmic reticulum and are implicated in stress response pathways. METHODS: Eight children from four consanguineous families residing in distinct geographies within the Middle East and Central Asia were recruited for study. All probands showed structurally similar microcephaly with lissencephaly (microlissencephaly) brain malformations. DNA samples from each family underwent whole exome sequencing, assessment for repeat expansions and confirmatory segregation analysis. RESULTS: An identical homozygous variant in (c.500G>A), encoding thioredoxin-related transmembrane protein 2, segregated with disease in all four families. This variant changed the last coding base of exon 6, and impacted mRNA stability. All patients presented with microlissencephaly, global developmental delay, intellectual disability and epilepsy. While is an activator of cellular repeat expansion toxicity, patients showed no evidence of repeat expansions. CONCLUSION: The c.500G>A allele associates with recessive microlissencephaly, and patients show no evidence of expansions. is the first PDI implicated in a recessive disease, suggesting a protein isomerisation defect in microlissencephaly.
Keywords: Amino Acid Sequence; Child; Child, Preschool; Consanguinity; Endoplasmic Reticulum; Exons; Female; Genetic Predisposition to Disease; Homozygote; Humans; Male; Membrane Proteins; Microcephaly; Mutation; Protein Disulfide-Isomerases; Protein Folding; Thioredoxins; Whole Exome Sequencing

Mutations in MBOAT7, Encoding Lysophosphatidylinositol Acyltransferase I, Lead to Intellectual Disability Accompanied by Epilepsy and Autistic Features. - Johansen, Anide; Rosti, Rasim O; Musaev, Damir; Sticca, Evan; Harripaul, Ricardo; Zaki, Maha; Çağlayan, Ahmet Okay; Azam, Matloob; Sultan, Tipu; Froukh, Tawfiq; Reis, André; Popp, Bernt; et al. (Am J Hum Genet, 2016)
The risk of epilepsy among individuals with intellectual disability (ID) is approximately ten times that of the general population. From a cohort of >5,000 families affected by neurodevelopmental disorders, we identified six consanguineous families harboring homozygous inactivating variants in MBOAT7, encoding lysophosphatidylinositol acyltransferase (LPIAT1). Subjects presented with ID frequently accompanied by epilepsy and autistic features. LPIAT1 is a membrane-bound phospholipid-remodeling enzyme that transfers arachidonic acid (AA) to lysophosphatidylinositol to produce AA-containing phosphatidylinositol. This study suggests a role for AA-containing phosphatidylinositols in the development of ID accompanied by epilepsy and autistic features.
Keywords: Acyltransferases; Arachidonic Acid; Autistic Disorder; Child; Child, Preschool; Consanguinity; Epilepsy; Female; Homozygote; Humans; Infant; Intellectual Disability; Lysophospholipids; Male; Membrane Proteins; Mutation; Pedigree; Phosphatidylinositols

Biallelic mutations in SNX14 cause a syndromic form of cerebellar atrophy and lysosome-autophagosome dysfunction. - Akizu, Naiara; Cantagrel, Vincent; Zaki, Maha S; Al-Gazali, Lihadh; Wang, Xin; Rosti, Rasim Ozgur; Dikoglu, Esra; Gelot, Antoinette Bernabe; Rosti, Basak; Vaux, Keith K; Scott, Eric M; Silhavy, Jennifer L; et al. (Nat Genet, 2015)
Pediatric-onset ataxias often present clinically as developmental delay and intellectual disability, with prominent cerebellar atrophy as a key neuroradiographic finding. Here we describe a new clinically distinguishable recessive syndrome in 12 families with cerebellar atrophy together with ataxia, coarsened facial features and intellectual disability, due to truncating mutations in the sorting nexin gene SNX14, encoding a ubiquitously expressed modular PX domain-containing sorting factor. We found SNX14 localized to lysosomes and associated with phosphatidylinositol (3,5)-bisphosphate, a key component of late endosomes/lysosomes. Patient-derived cells showed engorged lysosomes and a slower autophagosome clearance rate upon autophagy induction by starvation. Zebrafish morphants for snx14 showed dramatic loss of cerebellar parenchyma, accumulation of autophagosomes and activation of apoptosis. Our results characterize a unique ataxia syndrome due to biallelic SNX14 mutations leading to lysosome-autophagosome dysfunction.
Keywords: Animals; Atrophy; Autophagy; Cerebellar Diseases; Cerebellum; Child, Preschool; Female; Gene Frequency; Humans; Infant; Lod Score; Lysosomal Storage Diseases; Lysosomes; Male; Mutation; Phagosomes; Sorting Nexins; Spinocerebellar Ataxias; Syndrome; Zebrafish

Functional genome-wide siRNA screen identifies KIAA0586 as mutated in Joubert syndrome. - Roosing, Susanne; Hofree, Matan; Kim, Sehyun; Scott, Eric; Copeland, Brett; Romani, Marta; Silhavy, Jennifer L; Rosti, Rasim O; Schroth, Jana; Mazza, Tommaso; Miccinilli, Elide; Zaki, Maha S; et al. (Elife, 2015)
Defective primary ciliogenesis or cilium stability forms the basis of human ciliopathies, including Joubert syndrome (JS), with defective cerebellar vermis development. We performed a high-content genome-wide small interfering RNA (siRNA) screen to identify genes regulating ciliogenesis as candidates for JS. We analyzed results with a supervised-learning approach, using SYSCILIA gold standard, Cildb3.0, a centriole siRNA screen and the GTex project, identifying 591 likely candidates. Intersection of this data with whole exome results from 145 individuals with unexplained JS identified six families with predominantly compound heterozygous mutations in KIAA0586. A c.428del base deletion in 0.1% of the general population was found in trans with a second mutation in an additional set of 9 of 163 unexplained JS patients. KIAA0586 is an orthologue of chick Talpid3, required for ciliogenesis and Sonic hedgehog signaling. Our results uncover a relatively high frequency cause for JS and contribute a list of candidates for future gene discoveries in ciliopathies.
Keywords: Abnormalities, Multiple; Cell Cycle Proteins; Cerebellum; Eye Abnormalities; Gene Frequency; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Heterozygote; Humans; Kidney Diseases, Cystic; Mutant Proteins; Retina; RNA, Small Interfering

Exome sequencing links corticospinal motor neuron disease to common neurodegenerative disorders. - Novarino, Gaia; Fenstermaker, Ali G; Zaki, Maha S; Hofree, Matan; Silhavy, Jennifer L; Heiberg, Andrew D; Abdellateef, Mostafa; Rosti, Basak; Scott, Eric; Mansour, Lobna; Masri, Amira; Kayserili, Hülya; et al. (Science, 2014)
Hereditary spastic paraplegias (HSPs) are neurodegenerative motor neuron diseases characterized by progressive age-dependent loss of corticospinal motor tract function. Although the genetic basis is partly understood, only a fraction of cases can receive a genetic diagnosis, and a global view of HSP is lacking. By using whole-exome sequencing in combination with network analysis, we identified 18 previously unknown putative HSP genes and validated nearly all of these genes functionally or genetically. The pathways highlighted by these mutations link HSP to cellular transport, nucleotide metabolism, and synapse and axon development. Network analysis revealed a host of further candidate genes, of which three were mutated in our cohort. Our analysis links HSP to other neurodegenerative disorders and can facilitate gene discovery and mechanistic understanding of disease.
Keywords: Animals; Axons; Biological Transport; Cohort Studies; Exome; Gene Regulatory Networks; Genetic Association Studies; Humans; Motor Neuron Disease; Mutation; Neurons; Nucleotides; Pyramidal Tracts; Sequence Analysis, DNA; Spastic Paraplegia, Hereditary; Synapses; Transcriptome; Zebrafish